Responsibility of Land Deed Officials: Implications of Legal Convergence on the Harmonization and Integration of Collateral Law and Telematics Law - Nelly Azwarni Sinaga; Ida Nurlinda; Muhammad Yamin; Zaidar Zaidar (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
The dynamics of the convergence of telematics law within the national legal system, notably in the area of land, are represented by the Minister of Agrarian Affairs and Spatial Planning's Regulation Number 5 of 2020, which also serves as the head of the National Land Agency. One of the effects of land digitization is the Ministerial Regulation, which has changed the mortgage rights registration process from a traditional system to an electronic or digital one. Despite being virtual, the digitalization of Mortgage Rights registration involves actual legal actions with clear legal ramifications. The Land Deed Official is directly involved in the electronic execution of Mortgage Rights, which is governed by the Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency number 5 of 2020. The objective of this study is to investigate the consequences of the convergence of the Law on Mortgage Rights and the Telecommunication Law. This convergence results in the creation of digital-based Mortgage Rights via an integrated Electronic Mortgage Registration system, which is also known as the Electronic Mortgage System. The role and obligations of the Land Deed Official are also affected by this. This study employs a prescriptive, normative-juridical methodology. Based on the research findings, it is known that the conversion of the collateral registration system from a traditional system to a digital system is affected by the convergence of telematics legislation and the law of collateral guarantees. Because of the discord and breakdown of the Mortgage Law, the Electronic Information and Transactions Law, and the Regulations of the Land Deed Official, this also affects the status and legal obligations of the Land Deed Official, who fails to maintain the principle of justice..